Development of Animated Videos as a Medium for Learning Mathematics Class XI at State High School 2 Gomo - Amin Otoni Harefa; Agnes Renostini Harefa; Famati Zebua (CV. Rayyan Dwi Bharata, 2022)
Various obstacles in this study include students not being able to learn independently, the lack of teaching materials that can support learning, and the unavailability of animated video media as a mathematics learning medium. So that students wait for the teacher's presence in learning. This study aims to develop animated videos as a valid, practical and effective mathematical learning medium. This type of research is development research with the Plomp development model. Based on the results of the study, animated videos as mathematics learning media developed have been tested very valid by material validators with a percentage of 97.33%, linguists with a percentage of 100%, and media experts with a percentage of 93.04%, practicality levels with an average percentage of 94.81% and effectiveness levels with a percentage of 95.23% each categorized as very valid, practical and effective.